Determinants of barriers to the implementation of the chronic disease management program (PROLANIS) among patients with diabetes mellitus in Indonesia: A systematic literature review - Indah Koryah Indah; Elviera Gamelia; Suratman Suratman (Science Midwifery, 2026)
The Chronic Disease Management Program (PROLANIS) is a proactive healthcare service system developed by BPJS Kesehatan to manage chronic diseases, including diabetes mellitus (DM). Although the program has been implemented since 2014, its achievement remains far below optimal, with various barriers reported across different regions of Indonesia. This Systematic Literature Review aims to identify and synthesize the determinants of barriers to PROLANIS implementation among patients with diabetes mellitus in Indonesia. A literature search was conducted across PubMed, Scopus, and Google Scholar databases, covering the period 2021–2026. A total of 78 articles were identified, and following the PRISMA 2020 screening process, 22 studies met the inclusion criteria. Quality assessment was performed using the JBI Critical Appraisal Checklist. The results is barriers were identified across four principal dimensions: (a) the patient dimension, encompassing low knowledge levels, insufficient motivation, economic constraints, and distance to healthcare facilities; (b) the healthcare provider and primary care facility (FKTP) dimension, comprising limited human resources and inadequate infrastructure; (c) the BPJS system dimension, including frequently changing regulations and financing limitations; and (d) the environmental dimension, involving social support and cultural factors. The conclusion is barriers to PROLANIS DM implementation are multidimensional in nature. Comprehensive interventions targeting patient, provider, system, and environmental factors are required to improve program outcomes.